Conclusions: Past achievements and future directions for environmental policy research - Jörgens, H.; Knill, C.; Steinebach, Y. (Routledge handbook of environmental policy, 2023)
This chapter focuses on the challenge of long-term environmental policymaking, the role of cities and urban transformations in multi-level climate governance, and the turn towards complex policy mixes for addressing environmental challenges. Nevertheless, environmental policy studies have triggered many important research impulses in the political science subfields of policy analysis, comparative public policy, comparative politics, and global governance. In the field of public policy analysis, scholars have developed a series of theoretical concepts and analytical frameworks that today guide empirical research in various public policy domains. It has also advanced our understanding of the processes of the institutionalization of social movements, manifesting itself in the emergence of international environmental organizations and green parties.